Effects of Different Physical Training Protocols on Metabolic Syndrome Indicators and the Activity of Butyrylcholinesterase in Adolescents: A Randomized Clinical Trial - da Silva, Giuliano Roberto; Terra, Gerusa Dias Siqueira Vilela; de Oliveira, David Michel; Fernandes, Eduardo Vignoto; Zechin, Emerson José [UNESP]; Soares, Arthur Rizzi [UNESP]; Pessoa-Filho, Dalton Muller [UNESP]; Neiva, Cassiano Merussi [UNESP] (MDPI, 2024)
Metabolic syndrome (MS) increases the risk of cardiovascular disease and affects children and adolescents. Butyrylcholinesterase (BChE) is an enzyme associated with obesity. The aim of this study was to investigate the effects of different physical training protocols on MS indicators and their relationship with BChE activity. This randomized clinical trial included 80 adolescents randomly assigned to 4 groups (CG: Control Group; ATG: Aerobic Training Group; STG: Strength Training Group; and CTG: Concurrent Training Group). The EFC, lipid profile, glycemia, waist circumference, and blood pressure were analyzed. With the exception of the CG, all the groups underwent training protocols for 12 consecutive weeks, 4 times a week, as follows: (ATG: 75% of heart rate on an electric treadmill; STG: 85% of 1 maximum repetition; CTG: 20 min of aerobic training at the same intensity as the ATG, and 20 min of resistance training in the same way as the STG). The training reduced MS-related biomarkers, such as the lipid profile, glycemia, waist circumference, and blood pressure. STG reduced BChE activity. The training methods led to improvements in the majority of the MS indicators. In addition, aerobic training significantly reduced BChE activity after a 12-week training protocol. The results suggest that different types of exercise can benefit MS.
Keywords: butyrylcholinesterase; cardiometabolic syndrome; dyslipidemias; health of adolescents and youth; physical activity